2022
DOI: 10.1039/d2sm00638c
|View full text |Cite
|
Sign up to set email alerts
|

How friction and adhesion affect the mechanics of deep penetration in soft solids

Abstract: The mechanics of puncture and soft solid penetration is commonly explored with the assumption of frictionless contact between the needle (penetrator) and the specimen. This leads to the hypothesis of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Complications arise for quantification of W f in determination of the friction force per unit area, f , as an interfacial parameter (equation (2.7)). Alternatively, f can be expressed as f = ηp app [15,26], where p app is the average interfacial pressure between the puncture tool and the material, and η is the friction coefficient. It can be shown from the general form of the puncture energy presented by equation (2.22) that regardless of the constitutive model implemented, p app can be generally expressed as, normalized by the shear modulus, μ, papp=normal∂ΔEknormal∂d1μAnormalproj=A+Bcd,where A proj = π tan 2 θd 2 is the projection area of the puncture cone at d ; and A and B are dimensionless functions of θ and material failure properties.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Complications arise for quantification of W f in determination of the friction force per unit area, f , as an interfacial parameter (equation (2.7)). Alternatively, f can be expressed as f = ηp app [15,26], where p app is the average interfacial pressure between the puncture tool and the material, and η is the friction coefficient. It can be shown from the general form of the puncture energy presented by equation (2.22) that regardless of the constitutive model implemented, p app can be generally expressed as, normalized by the shear modulus, μ, papp=normal∂ΔEknormal∂d1μAnormalproj=A+Bcd,where A proj = π tan 2 θd 2 is the projection area of the puncture cone at d ; and A and B are dimensionless functions of θ and material failure properties.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental work has shown that η is highly sensitive to surface roughness, and such dependence is governed by a ‘true’ contact area at a microscale [62]. In biological tissues, contact mechanics can be even more complicated when the effects of surface adhesion [26,63], hierarchical structures [63], ornamentation [7,9,11,48] or lubrication [57] are introduced. Organic puncture tools such as mosquito proboscis [11], stingray barbs [9], parasitic wasp ovipositor [14], porcupine quill [48] and cactus spine [7] often exhibit morphological ornamentations or microstructured serrations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations